Eṉatu Yāḻppāṇamē - Caccitāṉantaṉ, Ka. (Kaṇapatippiḷḷai) (Kāntaḷakam, 1980)
On the 1977 communal violence that flared up during the International Conference-Seminar of Tamil Studies, 4th, Jaffna, 1974.